2014
DOI: 10.1182/blood-2013-12-545186
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging/angiography and transcranial Doppler velocities in sickle cell anemia: results from the SWiTCH trial

Abstract: • Children with SCA and stroke show severe parenchymal and vascular abnormalities that can be assessed using a vasculopathy grading scale. • Results from the SWiTCHTrial support concerns about ineffectiveness of transfusion therapy in preventing cerebrovascular injury progression.The Stroke With Transfusions Changing to Hydroxyurea (SWiTCH) trial compared standard (transfusions/chelation) to alternative (hydroxyurea/phlebotomy) treatment to prevent recurrent stroke and manage iron overload in children chronica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
83
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 38 publications
2
83
1
Order By: Relevance
“…66,67 Among children with SCA and progressive vasculopathy, 100% had evidence of new cerebral infarct within 5.5 years. 66 Despite the routine use of TCD to identify children with SCA at risk for overt strokes, several nuances of its use exist.…”
Section: Cns Vasculopathy Is Associated With Stroke and Scimentioning
confidence: 99%
“…66,67 Among children with SCA and progressive vasculopathy, 100% had evidence of new cerebral infarct within 5.5 years. 66 Despite the routine use of TCD to identify children with SCA at risk for overt strokes, several nuances of its use exist.…”
Section: Cns Vasculopathy Is Associated With Stroke and Scimentioning
confidence: 99%
“…It was concluded that transfusion/chelation remains the best way to manage children with SCA and stroke. 24 The next study, TWiTCH, 32,41,42 was a multicenter noninferiority trial in patients with a history of abnormal TCD and on chronic transfusion for at least 12 months who were randomized to transfusion pursuing vs hydroxyurea treatment. Started in 2011, it was prematurely closed in November 2014 41 because the primary end point had been reached and the strength of the statistical findings was unlikely to change with the collection of additional data.…”
Section: Discussionmentioning
confidence: 99%
“…Grading for stenosis (Table 1) was as described in the Stroke with Transfusions Changing to Hydroxyurea study. 24 Silent infarcts were defined as ischemic lesions of at least 3 mm by MRI in patients without a history of cerebrovascular events.…”
Section: Methodsmentioning
confidence: 99%
“…1 This study, which screened 161 children with sickle cell anemia (SCA) receiving chronic transfusion therapy for prevention of recurrent strokes, is the largest SCA cohort followed prospectively with magnetic resonance imaging (MRI) and magnetic resonance angiography (MRA) published to date, giving additional insights into the relationships between strokes and cerebral vasculopathy in SCA.…”
mentioning
confidence: 99%
“…3 The SWiTCH participants had a significant burden of vasculopathy: 69% of children demonstrated arterial stenosis at study entry. 1 Children with more severe vasculopathy were more likely to have low or uninterpretable transcranial Doppler ultrasound (TCD) velocities in the cerebral arteries, reinforcing that cerebral blood flow through these arterial territories is likely severely compromised. Not surprisingly, children with more severe arterial stenosis had a greater likelihood of cortical and subcortical infarctions.…”
mentioning
confidence: 99%